The Role of the People in the Amendment of the 1945 Constitution Based on Democratic Constitution Making: Future Prospects - Muhammad Nur Jamaluddin (Faculty of Law, Universitas Padjadjaran, 2020)
The amendments to the 1945 Constitution allegedly are not in line with the expectations of a democratic constitution. In fact, the role of the people in four amendments to the 1945 Constitution was very limited. The people who were involved in the amendment processes represented limited number of groups. Incidentally, only people with important and dominant powers were involved. The people were also not involved from the beginning of the amendment processes. Therefore, the role of the people in the amendments had not been carried out optimally. The results of the study show that the role of the people directly and actively in the amendment could increase transparency and public trust towards the government. The people are expected to be more responsive, accommodating, aspirational, and participatory to give rise to a match between the will of the people and the wishes of the government in the realization of the ideals of the Indonesian nation. The direct and active role of the people can be realized through conventional media, print media, and electronic media in a structured and systematic manner. It is expected that the people’s role will be able to strengthen the Indonesian constitutional system and economic, political, social, and cultural stability, as well as the defense and security of the Republic of Indonesia. In addition, the direct involvement of the people is expected to be in line with the optimization of the role of the Constitutional Court as the ‘guardian of the constitution’ to maintain the purity of the 1945 Constitution.Peran Rakyat dalam Perubahan Undang-Undang Dasar 1945 Berdasarkan Democratic Constitution Making: Prospek Masa Depan AbstrakPerubahan UUD 1945 yang telah dilakukan disinyalir masih jauh dari ekspektasi suatu pembentukan konstitusi yang demokratis. Faktanya, peran rakyat dalam 4 (empat) kali perubahan UUD 1945 sangatlah terbatas. Rakyat yang terlibat dalam proses amandemen hanya mewakili golongan tertentu saja dan notabene mempunyai kekuatan yang penting dan dominan. Rakyat juga tidak dilibatkan dari awal proses perubahan UUD 1945, sehingga peran rakyat dalam perubahan UUD 1945 secara aktif belum terlaksana secara optimal. Hasil penelitian menunjukkan bahwa peran rakyat secara langsung dan aktif dalam perubahan UUD 1945 dapat meningkatkan transparansi dan kepercayaan publik terhadap pemerintah. Rakyat diharapkan lebih responsif, akomodatif, aspiratif dan partisipatif sehingga akan terwujud kesesuaian antara kehendak rakyat dan keinginan pemerintah dalam mewujudkan cita-cita bangsa Indonesia. Peran rakyat secara langsung dan aktif dapat diwujudkan melalui media konvensional, media cetak bahkan media elektronik yang dilakukan secara terstruktur dan sistematis. Diharapkan dengan peran rakyat ini akan mampu memperkokoh sistem ketatanegaraan Indonesia, stabilitas ekonomi, politik, sosial, dan budaya serta pertahanan dan keamanan NKRI. Sebagai tambahan, pelibatan peran rakyat secara langsung ini diharapkan akan sejalan dengan optimalisasi peran Mahkamah Konstitusi sebagai institusi “pengawal konstitusi” guna tetap menjaga kemurnian UUD 1945.Kata kunci: Democratic Constitution Making, Prospek Masa Depan, UUD NKRI 1945.DOI: https://doi.org/10.22304/pjih.v7n1.a2